Optimalisasi Produk Kopi Lokal Merauke melalui Pelatihan Packaging dan Pemasaran Digital - Dodhy Hyronimus Ama Longgy; Putu Priyudahari, Bhujangga Ayu; Corry Lamtio Batubara; Yance Aima (Insan Kreasi Media, 2023)
The attention of the local government is focused on the development of local coffee products as part of efforts to empower the community for self-sufficiency and prosperity. Merauke coffee, especially Robusta coffee promoted by Seed Agung coffee farmers in the Muting district, is considered a superior commodity with significant potential for broader development and marketing. Despite being deemed a superior commodity with substantial potential, there are still obstacles in marketing, including a lack of attention to packaging and digital marketing literacy. The objective of this community service is to provide knowledge about the importance of packaging and the use of digital media as marketing tools to increase the sales of Muting Robusta coffee products. The method used in this community service follows the ABCD (Asset-Based Community Development) approach. This approach aims to maximize the potential of the coffee products owned by the Seed Agung village by providing insights and knowledge to the community about their assets. It emphasizes the importance of community empowerment and development to achieve the goals and dreams of the community. The results of this activity include the participants' understanding of the importance of packaging and digital marketing. In addition to discussing the stages of coffee maintenance and production, the training also teaches branding techniques and practical sales promotion using simple social media platforms such as WhatsApp, Facebook, and Instagram. This enables a wider audience to learn about Muting farmers' coffee products, expand market share, and hopefully boost the local economy.